Bio-inspired SME business strategy enriched by convergence of epistemology, neurobiology and cognitive psychology - Pereira, Joseph Errol (Eddie) (Curtin University, 2014)
The thesis addresses the development of an innovative bio-inspired solution for SME (Small Medium Enterprises) to overcome the problems preventing SME success in the global economy. The proposed solution is inspired by the DNA-studies in Human Biology and break-through Stem-cell research, regenerative medicine, tissue engineering; and presented with the strategy making epistemologies and its scientific foundation based on the “functional elements” that generate the bio-chemical strategies for human life and its analogy to SME development.